Left ventricular diastolic dysfunction in myocardial infarction and connective tissue dysplasia - M. E. Evsevyeva; O. N. Aleynik (Российский кардиологический журнал)
Hereditary heart connective tissue dysplasia (CTD) is one of the factors aggravating left ventricular diastolic dysfunction progression in working-age patients with myocardial infarction (MI). In individuals with MI and CTD, restrictive and pseudo-normal types of transmitral flow were prevalent, while patients with MI only were characterized by impaired relaxation.